Pengembangan Modul Praktikum Fisika Berbasis Open Ended Problem Pada Pokok Bahasan Getaran Harmonis - Dinni Wachidatun Niklah; Puji Hariati Winingsih; Ayu Fitri Amalia (Kappa Journal, 2020)
This study aims to develop and test the feasibility of physics practicum modules based on open ended problems on the subject of harmonic vibrations. This research type is research and development (R & D) by Sugiyono using 8 stages, namely potential and problems, data collection, product design, validation of practicum modules, improvement of practicum modules, practicum module trials, revision of practicum modules, and final products. The feasibility test for practicum module based on open ended problem uses a Likert scale questionnaire with validation by two validators. Research subjects MIPA MAN 5 Cirebon students, amounting to 9 students. The instrument used in the form of practical modules and questionnaire responses of students. The results of this research and development analysis were produced by practicum module products based on open ended problems on the subject of harmonic vibrations with an average validator score of 5.00 or (100%) with the Very Good (SB) category and the average score of students 4, 02 (80.40%) included in the Good category (B). So it can be concluded that the development of physics modules based on open ended problems is feasible to be used as practical teaching materials.DOI: 10.29408/kpj.v4i2.2652